The active commuting route environment scale (ACRES): development and evaluation - Stigell Erik; Wahlgren Lina; Schantz Peter (International Journal of Behavioral Nutrition and Physical Activity, 2010)
Abstract Background Route environments can be a potentially important factor in influencing people's behaviours in relation to active commuting. To better understand these possible relationships, assessments of route environments are needed. We therefore developed a scale; the Active Commuting Route Environment Scale (ACRES), for the assessment of bicyclists' and pedestrians' perceptions of their commuting route environments. Here we will report on the development and the results of validity and reliability assessments thereof. Methods Active commuters (n = 54) were recruited when they bicycled in Stockholm, Sweden. Traffic planning and environmental experts from the Municipality of Stockholm were assembled to form an expert panel (n = 24). The active commuters responded to the scale on two occasions, and the expert panel responded to it once. To test criterion-related validity, differences in ratings of the inner urban and suburban environments of Greater Stockholm were compared between the experts and the commuters. Furthermore, four items were compared with existing objective measures. Test-retest reproducibility was assessed with three types of analysis: order effect, typical error and intraclass correlation. Results There was a concordance in sizes and directions of differences in ratings of inner urban and suburban environments between the experts and the commuters. Furthermore, both groups' ratings were in line with existing objectively measured differences between the two environmental settings. Order effects between test and retest were observed in 6 of 36 items. The typical errors ranged from 0.93 to 2.54, and the intraclass correlation coefficients ranged from 'moderate' (0.42) to 'almost perfect' (0.87). Conclusions The ACRES was characterized by considerable criterion-related validity and reasonable test-retest reproducibility.